SECONDARY SCHOOL PRINCIPALS’ INSTRUCTIONAL LEADERSHIP APPROACHES IN ENHANCING LEARNERS’ ACADEMIC ACHIEVEMENT - mugambi, Murithi david (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The principal’s role is to promote students’ academic performance. The success or failure of a school is usually attributed to the principal. He or she is the pivot around which all aspects of the school revolve, being the person in charge of every detail of running the school, be it academic or administrative. A principal’s instructional leadership skills could make a difference in a learners’ achievement. It is imperative that the performance of a school is appraised against the accomplishments of the principal. So, the study evaluated secondary school principals’ instructional leadership approaches in enhancing learners’ academic achievement in Tigania West Sub-County. The study was guided by the following objectives: find out adequacy of teaching resources availed by the principals, assess the supervision of the use of teaching tools by the teachers and establish mentorship practices employed by the principals in enhancing academic achievement. The study used descriptive survey design to gather data on secondary school principals’ instructional leadership approaches in enhancing learners’ academic achievement. Using Krejecie and Cochran sample size tabulation model on the student and teachers populations of 637 and 55 yielded sample sizes of 240 and 50 respectively. The principals were picked purposively. The tools included the questionnaires, interviews and observations schedules. The study established that principals of high performing schools ensured that teachers prepared comprehensive schemes of work, updated lesson notes and documented records of work covered. Additionally, 80% of the principals from low performing schools did not motivate their students.. The study concluded that secondary school principals were inadequately prepared in mentorship skills. It was recommended that TSC in liaison with the MoE induct secondary school principals on mentorship programmes for learners and teachers. Key words: Principals, instructional leadership, academic achievement, teaching resources